2017
DOI: 10.1016/j.clml.2017.06.014
|View full text |Cite
|
Sign up to set email alerts
|

Immuno-oncologic Approaches: CAR-T Cells and Checkpoint Inhibitors

Abstract: Advances in understanding myeloma biology have shown that disease progression is not only the consequence of intrinsic tumor changes but also of interactions between the tumor and the microenvironment in which the cancer grows. The immune system is an important component of the tumor microenvironment in myeloma, and acting on the immune system is an appealing new treatment strategy. There are 2 ways to act toward immune cells and boost antitumor immunity: (1) to increase antitumor activity (acting on T and NK … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
22
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(23 citation statements)
references
References 80 publications
0
22
0
Order By: Relevance
“…Novel cell therapies and several potential targets for CAR T cells are under investigation in MM (45,46) (Table 2). Anti-CD38 and anti-SLAMF7 CAR T cells showed anti-MM effects in preclinical models (47,48), but the expression of both target antigens on other normal tissues including hematopoietic lineages and immune effector cells may cause off-tumor toxic effects limiting their long-term clinical use.…”
Section: T-cell Targets For Multiple Myelomamentioning
confidence: 99%
“…Novel cell therapies and several potential targets for CAR T cells are under investigation in MM (45,46) (Table 2). Anti-CD38 and anti-SLAMF7 CAR T cells showed anti-MM effects in preclinical models (47,48), but the expression of both target antigens on other normal tissues including hematopoietic lineages and immune effector cells may cause off-tumor toxic effects limiting their long-term clinical use.…”
Section: T-cell Targets For Multiple Myelomamentioning
confidence: 99%
“…This strategy will not only provide systemic immunity that is required for effective cancer immunotherapy (14), but may also increase local infiltration of T and NK cells in tumor microenvironment. In line with this idea, a recent review summarized the most recent clinical results on the use of checkpoint inhibitors and CAR-T cells in multiple myeloma (15). As such, multiple myeloma could be an appropriate candidate to test the idea of the combination therapy of checkpoint blockades with CAR-T therapy to increase infiltration of T cells in tumor microenvironment to overcome the resistance and thus to optimize the efficacy of immune checkpoint blockade therapy.…”
Section: Editorialmentioning
confidence: 99%
“…Despite the revolutionary therapeutic success in some solid malignancies and in Hodgkin's lymphoma, the role of check‐point inhibitors in MM remains controversial . Monotherapy with nivolumab had no relevant activity in RRMM .…”
mentioning
confidence: 99%
“…Notably, the rate of autoimmune disorders was significant in one study . Thus, several trials were initiated to evaluate various combinations of check‐point inhibitors with other agents (in particular IMIDs and MoAbs) . On July 3, 2017, however, the FDA placed a clinical hold on two phase III trials with pembrolizumab (KEYNOTE‐183 and KEYNOTE‐185) enrolling patients with RRMM and ordered the discontinuation of the lenalidomide/dexamethasone/pembrolizumab arm of another trial (KEYNOTE‐023), because interim results showed that pembrolizumab was associated with an unexplained increased risk for death.…”
mentioning
confidence: 99%
See 1 more Smart Citation